2022
DOI: 10.1186/s12906-022-03537-w
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine modalities used to treat adverse effects of anti-cancer treatment among children and young adults: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Dealing with the symptom burden of cancer diagnosis and treatment has led parents to seek different self-management strategies including Alternative and Complementary Medicine (CAM). The aim of this study was to perform a systematic review and meta-analysis about the use and effect of CAM modalities to treat adverse effects of conventional cancer treatment among children and young adults. Methods Six scientific research databases were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The goal of applying supportive care is to improve the quality of life of children with cancer and their families by treating the adverse effects caused by cancer treatment. Modalities such as acupuncture [ 15 , 16 , 57 59 ], massage [ 12 ], aromatherapy [ 60 ], healing [ 61 ], music [ 62 ], play therapy [ 63 ], and psychodrama [ 64 ] have beneficial outcomes in children [ 17 , 65 ]. In general, we found that supportive care modalities are used to provide comfort and control to the patients and parents; this is in line with other studies [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of applying supportive care is to improve the quality of life of children with cancer and their families by treating the adverse effects caused by cancer treatment. Modalities such as acupuncture [ 15 , 16 , 57 59 ], massage [ 12 ], aromatherapy [ 60 ], healing [ 61 ], music [ 62 ], play therapy [ 63 ], and psychodrama [ 64 ] have beneficial outcomes in children [ 17 , 65 ]. In general, we found that supportive care modalities are used to provide comfort and control to the patients and parents; this is in line with other studies [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that massage therapy [ 12 ] and acupuncture [ 15 , 16 ] among others provide benefits to children during cancer treatment. A systematic review of randomized controlled trials (RCT) from 2022 [ 17 ] showed that CAM, including acupuncture and hypnosis, reduces chemotherapy-induced nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our research teams conducted a systematic review of RCTs in 2021. 25 The systematic review aimed to review the research literature to identify any CAM modalities used to treat adverse effects of conventional cancer treatment among children and young adults. The meta-analysis showed that CAM (including acupuncture and hypnosis) was effective in reducing chemotherapy induced nausea and vomiting (CINV) in children and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis demonstrated that only 29% of the studies included reported data on safety. 25 Many studies about CAM modalities (ie, acupressure, healing touch, massage, music therapy, reiki) investigate effectiveness, but they do not address or report safety events among the reviewed studies. [26][27][28] In this review we want to investigate the safety of CAM modalities used to treat adverse effects of conventional cancer treatment in children and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are turning increasingly toward food supplements to improve well-being when pharmaceuticals fail [2,3]. Nowadays, nutraceuticals have received considerable interest due to their potential nutritional, safety, and therapeutic effects [4,5]. According to previous studies, many medicinal plants such as fenugreek, sumac, dill, ginger, grape, and green tea improve the lipid profile significantly [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%